2022
DOI: 10.3389/fnagi.2022.870326
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Regulation and Molecular Mechanism of Panax Ginseng Saponins on Senescence and Related Behaviors of Drosophila melanogaster

Abstract: In an increasingly aged global population, achieving healthy life expectancy through natural and safe drug interventions is highly desirable. Here we show that total ginsenosides (TGGR), the main active components in the traditional Chinese medicine, ginseng, promote longevity across species. In Drosophila, an intriguing effect of TGGR on lifespan was the relatively narrow treatment window to elicit long-term benefits. TGGR administration during early adulthood, and especially during midlife, was sufficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…32 Our data showed that 120 μM puerarin supplementation significantly upregulated the ATP content in all flies, implying that puerarin promotes longevity by enhancing ATP production. Moreover, stress tolerance is beneficial for advancing the longevity of Drosophila 33 by modulating the expressions of DMP53, CAT, SOD1, HSP70, and Methuselah. 2,34,35 We found that puerarin supplementation increased the survival time of flies from starvation and oxidation by enhancing the levels of DMP53, CAT, and SOD1, implying that puerarin extends the lifespan of Drosophila by improving resistance to stress.…”
Section: Discussionmentioning
confidence: 99%
“…32 Our data showed that 120 μM puerarin supplementation significantly upregulated the ATP content in all flies, implying that puerarin promotes longevity by enhancing ATP production. Moreover, stress tolerance is beneficial for advancing the longevity of Drosophila 33 by modulating the expressions of DMP53, CAT, SOD1, HSP70, and Methuselah. 2,34,35 We found that puerarin supplementation increased the survival time of flies from starvation and oxidation by enhancing the levels of DMP53, CAT, and SOD1, implying that puerarin extends the lifespan of Drosophila by improving resistance to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, autophagy, a form of cellular degradation, aids in nutrient recycling and keeps cells in balance (192). The autophagy signaling system includes the phosphoinositide 3-kinase (PI3K)-Akt pathway, which elevates levels of the autophagy inhibitor target of rapamycin (TOR) (193). Under normal development conditions, TOR is active and phosphorylates the Autophagy-Related (Atg) 13 protein several times.…”
Section: The Autophagy Immune Pathwaymentioning
confidence: 99%
“…Historically, ginseng is known as the "king of herbs" and has been widely used to treat various diseases. For example, it was used to slow down the aging process through DNA protection achieved by the reduction in oxidative stress and regulation of intestinal microorganisms [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%